Analysis of public responses to political controversies in the beauty industry: A case study of Rose All Day and Esqa Brand owners in support of Israel - Nazahra, Gusti Nadya (Universitas Wiralodra, 2024)
On October 30, 2023, Indonesia's beauty industry was shocked by the boycott of two well-known local brands, ESQA and Rose All Day. The trigger for this boycott was the actions of the owners of the two brands, Angelina Cindy and Tiffany Danielle, who gave support to Israel by